Effect of garlic powder (Allium sativum) on growth, dressing parameters, serum biochemical contents and profitability of broiler (Bangladesh Journal of Animal Science, 2018)
This study was conducted to evaluate the effect of garlic an alternative feed additive in broiler diet.  The experiment was carried out for a period of 32 days with a number of 340 day-old straight run broiler chicks. Birds were divided into five dietary treatment groups with 4 replications each having 17 birds. The dietary groups were; control (basal diet; no additives), antibiotic (basal diet + antibiotic), garlic 0.25% (basal diet + 0.25% garlic powder), garlic 0.50% (basal diet + 0.50% garlic powder) and garlic 0.75% (basal diet + 0.75% garlic powder). Results showed that the body weight, body weight gain and total FCR were not differ significantly (P>0.05) among the treatment groups. Total feed intake in different dietary levels showed significant (P